The Impact of Political Connection on Tax Avoidance; A Literature Review - I Gusti Putu Eka Rustiana Dewi; A.A Sagung Istri Pramanaswari (Jurnal Minfo Polgan, 2024)
Political power has a big impact on tax legislation and tax avoidance methods. The impact of political connections on tax avoidance in Indonesia has raised significant concerns among policymakers, regulators, investors, and stakeholders. The research method is literature review research, using descriptive qualitative data technic analysis. The data used in the study is secondary data obtained through some journals such as national and international that provide previous research, book references, internet site references, news in national references, and international media references as well as various state reports related to understanding the relationship between political connections and tax avoidance is essential for developing a comprehensive framework for addressing possible abuses and ensuring fairness and transparency in the tax system. The research contributes to analyzing the strong correlation between political relations and tax avoidance.